Characteristics of acoustic gravity waves obtained from Dynasonde data. Issue 4 (23rd April 2016) - Negrea, Cătălin; Zabotin, Nikolay; Bullett, Terrence; Fuller‐Rowell, Tim; Fang, Tzu‐Wei; Codrescu, Mihail
Abstract: Traveling ionospheric disturbances (TIDs) are ubiquitous in the thermosphere‐ionosphere and are often assumed to be caused by acoustic gravity waves (AGWs). This study performs an analysis of the TID and AGW activity above Wallops Island, VA, during October 2013. The variations in electron density and ionospheric tilts obtained with the Dynasonde technique are used as primary indicators of wave activity. The temporal and spectral characteristics of the data are discussed in detail, using also results of the Whole Atmosphere Model (WAM) and the Global Ionosphere Plasmasphere Model (GIP). The full set of propagation parameters (frequency, and the vertical, zonal and meridional wave vector components) of the TIDs is determined over the 160–220 km height range. A test of the self‐consistency of these results within the confines of the theoretical AGW dispersion relation is devised. This is applied to a sample data set of 24 October 2013. A remarkable agreement has been achieved for wave periods between 52 and 21 min, for which we can rigorously claim the TIDs are caused by underlying acoustic gravity waves. The Wallops Island Dynasonde can operate for extended periods at a 2 min cadence, allowing determination of the statistical distributions of propagation parameters. A dominant population of TIDs is identified in the frequency band below 1 mHz, and for it, the distributions of the horizontal wavelengths, vertical wavelengths, and horizontal phase speeds are obtained. Key Points: Characteristics of acoustic gravity waves at Wallops Island Comparison with theoretical dispersion relation Propagation characteristics of traveling ionospheric disturbances